Attention Deficit Hyperactivity Disorder Symptoms Among Medical Students at the University of Belgrade - Detection And Association With Sociodemographic Characteristics, Academic Achievements and Loneliness - Kojović, Natalija; Srpski, Srpski; Srpski, Srpski; Srpski, Srpski (Medicinski podmladak, 2024)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a psychiatric disorder with typical childhood onset. Mental disorders, social difficulties and dysfunction may or may not resolve in adulthood. To detect ADHD symptoms in adult population, appropriate instruments have been developed wich havenʼt been applied on students in Serbia.The Aim: To find prevalence of positive detection of ADHD symptoms among medical students and the association with sociodemographic characteristics, academic achievements and loneliness.Material and Methods: A cross-sectional study was conducted at the University of Belgrade Faculty of Medicine by distributing a questionnaire online. It gathered data on socio-demographic and academic characteristics of the participants. For ADHD symptoms  screening we used ASRS-v1.1. Also we used Scale of Subjective Social Status and Hughes Loneliness Scale. Data were analyzed using descriptive and analytical statistical methods.Results: The sample consisted of n=404 students of all years of the university (age 18-30 years). A total of 21.7% of the students had positive detection of ADHD symptoms. Among them, the average mark during studies was 8.5±0.8, while in the other group, it was 8.7±0.7 (p=0.009). Students with a positive detection were lonelier (p